Analysis on Influences of College Students’ Psychological Capital in Entrepreneurial Learning Engagement - Zhang, Baoge; Xu, Qiuyan; Han, Song; Jiao, Lan (Frontiers in Psychology, 2020)
College students’ entrepreneurial learning engagement (ELE) is a key link that affects the success of future entrepreneurship. To analyze the influencing factors of the psychological capital (PC) dimension in college students’ ELE, a total of 211 college students were selected from colleges in the Ningbo area for questionnaire survey. The principal component analysis method was used to test the difference validity of PC and ELE. One-way analysis of variance was used to analyze differences in demographic variables between PC, ELE, and positive emotions (PEs). Besides, the structural equation model was used to analyze the mediating role of PEs in PC and ELE. In addition, there was a significant difference between the unrestricted model of PC-ELE and the restricted model (p < 0.05), and the difference between the potential dimensions of “mental capital-learning input” was generally satisfactory; there were significant differences at the professional level (p< 0.01); PC had significant differences in family economic status (p <0.01); the indirect path coefficients of PE added to the relationship between PC and ELE were 0.106 and 0.211, respectively, and there was no significance (p > 0.05). In short, the PC of college students has an significant positive effect (PI) on ELE, PC differs significantly in family economic status, and PEs differ significantly at the professional level. The research results show that there is no mediating effect of PEs in the relationship between PC and college students’ ELE.